Evaluating Progress Toward Healthy People 2010 National Diabetes Objectives - Dara Murphy, MPH; Mark Rivera, PhD; Maurice Martin, PhD; Leonard Jack, Jr, PhD, MSc; Qaiser Mukhtar, PhD (Centers for Disease Control and Prevention, 2006)
IntroductionIn 1999, the National Diabetes Prevention and Control Program at the Centers for Disease Control and Prevention and its 59 Diabetes Prevention and Control Programs adopted five Healthy People 2010 objectives. These objectives aim to improve the rates of preventive care services among people with diabetes and include annual foot examinations, hemoglobin A1c tests, and annual dilated eye examinations. This paper examines progress toward meeting these three objectives.MethodsQuestions from the diabetes module of the Behavioral Risk Factor Surveillance System (BRFSS) were used to evaluate changes in age-adjusted rates for annual foot examinations, hemoglobin A1c tests, and annual dilated eye examinations of 44 jurisdictions between 2000 and 2003. Questions from the diabetes module were also used to compare percentage rates of 47 jurisdictions in 2003 with Healthy People 2010 percentage targets.ResultsFrom 2000 to 2003, for the 44 jurisdictions, the aggregate, age-adjusted rate of annual foot examinations increased from 63.7% to 69.3% (P < .001); the rate of self-reported hemoglobin A1c tests increased from 68.3% to 69.5% (P = .35); and the rate of annual dilated eye examinations decreased from 67.7% to 65.2% (P = .05). In 2003, 20 of 47 jurisdictions met the Healthy People 2010 target for foot or eye examinations, and all 47 jurisdictions met the target for hemoglobin A1c tests. An inverse association was found between baseline rates in 2000 and the magnitude of change from 2000 to 2003 for all three national diabetes objectives.ConclusionThe National Diabetes Prevention and Control Program should consider adopting additional Healthy People 2010 objectives. Baseline rates should be considered in 1) selecting objectives, 2) setting percentage targets, and 3) evaluating current or future objectives. Program-related information should be linked with traditional data sources such as BRFSS so that we can understand the role of environmental factors and evaluate progress of jurisdictions toward national diabetes objectives.